Symptoms and Treatment of Low Blood Glucose - Linda Bobroff (EDIS, 2018)
Low blood glucose, also called hypoglycemia, can be life-threatening for people with diabetes. It can be caused by eating too little food, taking too much insulin or other diabetes medication, or being extra active. If left untreated, low blood glucose can progress to diabetic coma. Everyone with diabetes needs to know the symptoms of low blood glucose so they can take action right away. This 2-page fact sheet discusses preparation, symptoms, and treatment. Written by Linda B. Bobroff, and published by the UF/IFAS Department of Family, Youth and Community Sciences, revised February 2018. http://edis.ifas.ufl.edu/fy521